1984
DOI: 10.1113/jphysiol.1984.sp015269
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cholinergic activation and desensitization at snake twitch and slow muscle fibre end‐plates.

Abstract: SUMMARY1. Characteristics of receptor-channel activation and desensitization have been compared at voltage-clamped snake slow and twitch fibre end-plates maintained in an isotonic potassium propionate solution.2. Miniature end-plate current (m.e.p.c.) decay was slower and less voltage dependent at slow fibre end-plates than at twitch fibre end-plates. The peak m.e.p.c. amplitude versus voltage relationship and reversal potential were similar at the two end-plate types.3. Acetylcholine-induced noise and m.e.p.c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 19 publications
2
62
0
Order By: Relevance
“…and carbachol (CCh)-induced current (e.p.c.cch). We also have shown that the kinetics of receptor channel gating and desensitization are similar to those found in preparations maintained in a sodium containing solution (Dionne & Parsons, 1981;Connor et al, 1984).…”
Section: Generalmentioning
confidence: 51%
See 4 more Smart Citations
“…and carbachol (CCh)-induced current (e.p.c.cch). We also have shown that the kinetics of receptor channel gating and desensitization are similar to those found in preparations maintained in a sodium containing solution (Dionne & Parsons, 1981;Connor et al, 1984).…”
Section: Generalmentioning
confidence: 51%
“…First, at positive membrane potentials, the peak carbachol-induced current (e.p.c.cCh) amplitude is less than that produced at negative potentials which allows for better voltage control over a wider range of agonist concentrations (Connor et al, 1984;Colquhoun & Ogden, 1988). Second, the fast rate of desensitization (time constant in seconds) is slowed at positive membrane potentials (Fiekers et al, 1980;Cachelin & Colquhoun, 1989).…”
Section: Generalmentioning
confidence: 99%
See 3 more Smart Citations